Changing the adhesion force for testing road vehicles at safe speed - Jilek, Petr; Němec, Jan (Latvia University of Afgriculture, 2020)
The article deals with various ways of bringing a car to the stability limit in terms of adhesion conditions. The article deals with the possibilities how to reduce the adhesion force transmitted between the car wheels and the road. Subsequently, we evaluate the change in the behaviour of the car depending on the way the adhesion force changes. The measurement is carried out on a special experimental vehicle. The aim of the article is to find the differences in the car behaviour when inducing a limit situation. In the first case, by reducing the coefficient of adhesion and, in the second case, by reducing the radial response on the car wheels. The change of the coefficient of adhesion is done by means of a sliding surface (foil) sprayed with water. To reduce the radial response on vehicle wheels, we used a device called Alternative SkidCar. It is similar to a commercially available SkidCar device that is built for a particular experimental vehicle.The car behaviour in both cases was verified on the basis of driving tests in a direct direction. The actual test was carried out in the form of critical braking. Initial set of measurements was realized for dry road and separate vehicle. Subsequently, we proceeded to the experiment on the sliding surface. The coefficient of adhesion is reduced to a constant value on the sliding surface. The last set of experimental tests was performed with the help of Alternative SkidCar. We carried out the initial measurements for a situation where the car wheels transmitted a full radial response. In this way we found out to what extent the frame of the Alternative SkidCar influences the car behaviour. Furthermore, we reduced the radial response of vehicle wheels in three stages. Subsequently, we processed the measured values and, by comparison, we found differences from comparable tests. Due to the reduced adhesion force, a limit state in relation to stability at lower speeds can be induced on the vehicle. In this way, it is possible to achieve skid at a lower, so-called safe speed. © 2020 Latvia University of Life Sciences and Technologies. All rights reserved.
Možnosti změny adhezní síly a její vliv na chování silničního vozidla při jízdě na mezi stability
Keywords: adhesion force; critical braking; radial reactions; road vehicle; stability limit; adhezní síla; panické brzdění; radiální reakce; silniční vozidlo; stabilita vozidla